Effects of types and degrees of ankylosing spondylitis hip structural damages on post-total hip arthroplasty outcome measurements. Issue 46 (13th November 2020) - Man, Siliang; Ji, Xiaojian; Zhang, Liang; Hu, Zhengyuan; Lv, Yanwei; Zhou, Yixin; Song, Hui; Huang, Feng
Abstract : Abstract: To determine the effects of ankylosing spondylitis (AS)-associated hip damages on the outcome measurements after total hip arthroplasty (THA). The medical records of 122 patients with AS (181 hips) who underwent THA were retrospectively reviewed. The mean follow-up was 43.9 (32–129) months. The types and degrees of hip damages were evaluated by preoperative hip X-rays. The patients were grouped according to the satisfaction degree after the operation. Univariable and multivariable statistical analyses were conducted. The intraclass correlation coefficients for the assessment between the 2 reviewers in the study were 0.86 to 0.97. Cox regression showed that femoral head erosion severity had an effect on the recovery time of independent walking without crutches postoperatively (odds ratio = 1.467, 95% confidence interval: 1.050–2.409, P = .025). The mean time to recover independent walking in the severe femoral head erosion group was 7.3 ± 0.9 weeks, which was 4.6 ± 0.4 weeks longer than in the non-severe femoral head erosion group, as confirmed by the log-rank (Mantel–Cox) test (Chi-squared = 11.684, P = .001). The multivariable analysis showed that higher acetabular sclerosis scores correlated with lower postoperative dissatisfaction risk (odds ratio = 0.322, 95% confidence interval: 0.136–0.764). The multiple linear regression analysis showed that postoperative range of motion (ROM) improvement was affected by preoperative ROM of the hip, space narrowing degree, and ceramic-ceramic material for the weight-bearing surface (F = 179.81, P < .001), with preoperative ROM of the hip having the greatest impact. Severe femoral head erosion prolongs the recovery time of independent walking after THA. Acetabular sclerosis is not associated with poor outcomes in patients with AS-associated hip damage undergoing THA. Abstract : Supplemental Digital Content is available in the text